The effect of usefulness, ease of use, and trust on purchase intention of online buying / Siti Zaharah Mohamadti - Mohamadti, Siti Zaharah
The purpose of this study was to explore the effects of usefulness, ease of use, and trust on that supported by the Technology Acceptance Model (TAM) purchase intention of online buying. The subjects of this study were selected from the residents of Alor Setar, Kedah. Questionnaire was the major tool of this study. After questionnaire collection, the number of valid questionnaire was 310. The structural equation of statistics was utilized for data analysis. The result were obtained as followings: Perceived usefulness would positively influence the purchase intention on buying online. Perceived ease of use has negative influence to the purchase intention through online and perceived of trust have a positive influence to the purchase intention on online buying.